Exploiting Similarities as Internationalization Strategy: A Case of MR.DIY Successful Expansion into the Indonesian Market - Ainin Atirah Zulkarnain (Universitas Airlangga, 2023)
It has been widely known that multinational national enterprises (MNEs) have been part of important agencies playing a critical role in determining global governance. Increasing globalization which comes out in various forms has crucially facilitated the operation of MNEs globally as well as increased MNEs’ influence on global politics. However, similarities and differences that could come in the forms of culture, politics, geography, and economy, are still critical hindrances for MNEs competing internationally. Building and employing a spot-on internationalization strategy, therefore, becomes a crucial issue. Using MR. DIY’s successful expansion into the Indonesian market as a case, this article highlights how cultural adaptation could become a key success for an MNEs’ global expansion. Equally, it reveals how far culture is needed by MR. DIY’s when doing its international expansion into the Indonesian market. The case informed that some similarities in cultural elements can be instrumental requisites supporting the success of exploiting cultural similarities as an internationalization strategy. These cultural elements are potential sources for adjustment steps with local culture through the adaptation process. Keywords: COVID-19; Diplomasi vaksin; Belt and Road Initiative (BRI); Mask Diplomacy; MENA